Penerapan Algoritma Stemming Nazief-Adriani dengan Metode Cosine Similarity Dalam Aplikasi Ujian Esai - Mohamad Arif Suryawan; LM. Fajar Israwan; Ferdianto Arland (Prosiding SISFOTEK, 2024)
Essay exam assessment using an exam application takes a long time to check. Answer checking is done by reading carefully. The answers given are some that match the answer key, and some are very different. Therefore, an exam application is needed that can directly assess the essay question answers and then give a score according to the answers written. This study aims to apply the Nazief-Adriani stemming algorithm with the Cosine Similarity method to the high school essay exam application. The research method used in this study consists of two stages, first the Nazief-Adriani algorithm carries out several processes, namely normalizing lowercase letters, punctuation, separating into individual words, removing common words, stemming by removing affixes from root words, mapping synonyms and finally calculating the frequency of word occurrence. Furthermore, the second stage, the Cosine Similarity method is used to compare the level of similarity with the answer key. This study produces an exam application that applies the Nazief-Adriani stemming algorithm in checking essay answers. This exam application is Android-based so that it makes it easier to answer exam questions, the answers are written in the box provided. The essay exam questions that are given are first equipped with the answer key stored in the application. From testing three essay answers, the calculation results using the Cosine Similarity method were obtained, namely: the first answer is 94.3, the second answer is 94.3, and the third answer is 74.5. The first and second answers produce a value of 94.3, indicating a high level of similarity to the answer key. Thus, the application created is expected to make it easier to check answers to essay questions quickly and accurately.